495. UNIPORTAL VATS MCKEOWN ESOPHAGECTOMY: 4-YEAR EXPERIENCE FROM A TERTIARY CARE CENTER. (24th September 2022) - Rajan, Shiv; Kumar, Vijay
Abstract: A multidisciplinary approach is a cornerstone for the management of the carcinoma esophagus. Minimally Invasive Surgery (Total or hybrid) is essential for better postoperative outcomes. VATS assisted McKeown MIE is a well-established procedure. With the introduction of the uniportal VATS technique in lung surgeries, there is an increasing interest to replicate this in MIE too. Here we appraise our initial experience with the uniportal VATS (uVATS) MIE for the locally advanced squamous cell esophageal cancer. This is a retrospective observational study. The cohort of carcinoma esophagus patients who underwent surgery from January 2018 to February 2022 in the department of surgical oncology was studied. Demographic data, clinical, treatment details, postoperative complications and short term oncological outcomes of patients who underwent the uVATS technique in semi-prone position were analyzed. Total 32 (49.2%) patients underwent uVATS Mckeown esophagectomy. The majority of the patients had SCC (63%). All patients received NACT+/-RT. Each underwent extended mediastinal lymphadenectomy except two patients who had additional cervical lymphadenectomy. The mean thoracic phase time was 112+/- 25 min & blood loss was 115 +/- 20 ml. The median thoracic nodes dissected was 15 (8-36), postoperative pain score was 4 and hospitalization duration was 9 (8-12) days. Two patients had pneumonia and 2 had other complications. There was no 30-day mortality. After the median follow-up of 26.8 months, the OS & DFS was 93% & 86% respectively. uVATS in a semi-prone position with fourth intercostals space access incision is a feasible and safe technique. It has all the advantages of MIE techniques over open surgery. The coaxial operating axis provides the best manipulation zone for operating without the need for CO2. Conversion to thoracotomy is quick if required. We believe it has a short learning curve than multiport VATS. More studies are needed to generate data for the uVATS technique in future.